Consignas y carnaval en el movimiento estudiantil colombiano: una disputa por lo social - Vargas Torres, Margarita Rosa (2020)
This article is divided in three parts. In the first one, a brief description is made of the context in which the discussion about a specific manifestation of the student movement takes place, such as slogans, and their capacity to express and produce subjectivity, as well as their capacity to make educational problems visible. In the second part, it is suggested that the slogans and the carnival-like forms in which the student movement enunciates them, produce and express political subjectivity, which is understood as the construction of other meanings alternative to those of the neoliberal hegemonic order. These slogans ultimately express claims of the students movement. The third part focuses on the carnival practices of the student movement and their implications.